Aplastic anemia in pregnancy: an unequivocal nightmare for the obstetricians - M., Ponn Malar Janani; Rajan, Niranjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Aplastic anemia is a rare blood disorder characterized by pancytopenia and hypocellular bone marrow. It is a serious, life-threatening condition that may manifest during pregnancy and imposes a great challenge on management. The major causes of morbidity and mortality are hemorrhage and sepsis. The present case report describes our experience with a pregnant patient with aplastic anemia who was managed with hematologist support, leading to a successful outcome. A 26-year-old primigravida with no significant previous medical history was diagnosed with aplastic anemia at 22 weeks of gestation. She was managed with multiple erythrocytes, platelet transfusion, eltrombopeg, prednisolone, and immunosuppressive therapy. At 34 weeks of gestation, she underwent an elective caesarean section under general anesthesia for a severe intrauterine growth-restricted fetus. The postpartum period was uneventful. Management of aplastic anemia in pregnancy remains controversial, with no clear guidelines as there are only a few case reports. Hence, it warrants a comprehensive multidisciplinary-team approach in order to devise an obstetric, hematological, anesthetic, and neonatal plan and anticipate complications during the peripartum period. And it is possible to have a successful outcome with recent advances in supportive care and blood transfusions. This case is discussed because of its rarity and highlights the challenges involved in its diagnosis, treatment, and follow-up.